Analisis Mazmur 3 Untuk Praktik Konseling Krisis - Mustika, Maria Benedetta; Objantoro, Enggar (Sekolah Tinggi Teologi Kharisma, 2020)
The Book of Psalms is one of the books that has many references about the crisis of life, one of which is Psalm 3. Therefore, the author feels it is necessary to examine how the use of Psalm 3 to be a reference for the implementation of crisis counseling. The author uses the method of analyzing the Book of Psalms to get the true meaning of the text of Psalm 3. So as to obtain the results that Psalm 3 can be used to counsel people who are bullied, experience sadness, loneliness, worthlessness and feel rejected. The conviction held by David that God never left him also needed to be implanted in the hearts of counselees who experienced a situation like this. Kitab Mazmur merupakan salah satu kitab yang memiliki banyak referensi mengenai krisis hidup, salah satunya adalah Mazmur 3. Oleh sebab itu penulis merasa perlu diteliti bagaimana pemanfaatan Mazmur 3 untuk menjadi acuan bagi pelaksanaan konseling krisis. Penulis menggunakan metode analisis Kitab Mazmur untuk mendapatkan makna sesungguhnya dari teks Mazmur 3. Sehingga memperoleh hasil bahwa Mazmur 3 dapat digunakan untuk mengkonseling orang-orang yang di-bully, mengalami kesedihan, kesepian, tidak berharga dan merasa tertolak. Keyakinan yang dimiliki oleh Daud bahwa Tuhan tidak pernah meninggalkan dia juga perlu ditanamkan dalam hati konseli yang mengalami situasi seperti ini.